Electrochemical and Photoelectrochemical Properties of Screen-Printed Nickel Oxide Thin Films Obtained from Precursor Pastes with Different Compositions. Issue 2 (1st January 2017) - Bonomo, Matteo; Naponiello, Gaia; Venditti, Iole; Zardetto, Valerio; Carlo, Aldo Di; Dini, Danilo
Abstract : In this work we present the electrochemical and photoelectrochemical characterization of NiO thin films [thickness ( l ) range: 2 ≤ l ≤ 4 μm], which have been obtained from screen-printing of three precursor-pastes. All three pastes contained preformed NiO nanoparticles [diameter (Ø) range: 20 < Ø < 50 nm], but differed for the content and nature of the acidic component. The resulting NiO samples were employed as photoactive cathodes of p -type dye-sensitized solar cells ( p -DSCs). The temperature of sintering was kept below 450°C to warrant mesoporosity and electrical connectivity between the nanostructured domains while maintaining a good level of adhesion on the substrate. The photoelectrochemical properties of bare and erythrosine b (ERY)-sensitized NiO in p -DSCs depended on the composition of the screen-printing paste. The NiO samples obtained from the pastes with the lowest amount of acidic component or containing the acid with the stronger character, namely HCl, gave the best performances in the corresponding p -DSCs. In the series of ERY-based p -DSCs here tested the most performing screen-printed electrode gave the largest overall conversion efficiency ( η > 0.04%) and highest external quantum efficiency (EQE > 9% at 830 nm) with respect to the p -DSCs with NiO photocathodes of similar thickness, which have been prepared via different methods of deposition.